2016
DOI: 10.1371/journal.pone.0163046
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Links Oxidative Stress to Impaired Pancreatic Beta-Cell Function Caused by Human Oxidized LDL

Abstract: Elevated plasma concentration of the pro-atherogenic oxidized low density lipoprotein cholesterol (LDL) triggers adverse effects in pancreatic beta-cells and is associated with type 2 diabetes. Here, we investigated whether the endoplasmic reticulum (ER) stress is a key player coupling oxidative stress to beta-cell dysfunction and death elicited by human oxidized LDL. We found that human oxidized LDL activates ER stress as evidenced by the activation of the inositol requiring 1α, and the elevated expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 41 publications
(84 reference statements)
2
52
0
Order By: Relevance
“…Recent studies support the view that ER protein folding pathways are highly correlated with ROS production [4,87]. In ER, redox homeostasis is crucial for the protein folding process and disulfide bond formation [89].…”
Section: Vicious Sequence Of Events Between Endoplasmic Reticulum mentioning
confidence: 90%
“…Recent studies support the view that ER protein folding pathways are highly correlated with ROS production [4,87]. In ER, redox homeostasis is crucial for the protein folding process and disulfide bond formation [89].…”
Section: Vicious Sequence Of Events Between Endoplasmic Reticulum mentioning
confidence: 90%
“…These sensors signal and initiate transcriptional and translational programs related to amelioration of the stress, including silencing of most protein synthesis and augmenting the synthesis of chaperone molecules, promoting proteasome‐mediated degradation. In cases where these unfolding protein response elements (UPREs: PERK, IRE1 and ATF6) are unable to overcome the stress, apoptotic pathways are activated . Chemical inhibition of sEH and genetic deletion has been demonstrated to decrease ER stress .…”
Section: Discussionmentioning
confidence: 99%
“…PERK, IRE1 and ATF6) are unable to overcome the stress, apoptotic pathways are activated. [48][49][50][51][52][53] Chemical inhibition of sEH and genetic deletion has been demonstrated to decrease ER stress. [53][54][55] The cardioprotective effect of sEH inhibitors in this model could therefore be due to mitigation of ER stress.…”
Section: Treatment With Seh Inhibitors Decreases Endothelial Dysfunmentioning
confidence: 99%
“…Recent studies have suggested that ER signalling pathways correlate with ROS production. 26,45,46 In response to ERS, the activation of CHOP was shown to promote ROS production and to indirectly disturb reduction-oxidation (redox) homeostasis causing further induction of oxidative stress. 47,48 In addition, ROS has also been reported to induce ERS that is involved in the CHOP-Wnt pathway.…”
Section: Discussionmentioning
confidence: 99%